2018
DOI: 10.1186/s12940-018-0400-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between mixtures of urinary phthalate metabolites with gestational age at delivery: a time to event analysis using summative phthalate risk scores

Abstract: BackgroundPreterm birth is a significant public health concern and exposure to phthalates has been shown to be associated with an increased odds of preterm birth. Even modest reductions in gestational age at delivery could entail morbid consequences for the neonate and analyzing data with this additional information may be useful. In the present analysis, we consider gestational age at delivery as our outcome of interest and examine associations with multiple phthalates.MethodsWomen were recruited early in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Therefore these eicosanoids may be up-regulated in disease states involving cardiovascular irregularities, an important precursor for adverse pregnancy outcomes 14 . Among the environmental exposures, we also showed that phthalates have been associated with increased risk for preterm delivery and reduced gestational age at delivery within the LIFECODES cohort 15,16 . Based on these previous studies, there is circumstantial evidence of potential mediation between prenatal phthalate exposure and pregnancy outcomes through eicosanoids.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore these eicosanoids may be up-regulated in disease states involving cardiovascular irregularities, an important precursor for adverse pregnancy outcomes 14 . Among the environmental exposures, we also showed that phthalates have been associated with increased risk for preterm delivery and reduced gestational age at delivery within the LIFECODES cohort 15,16 . Based on these previous studies, there is circumstantial evidence of potential mediation between prenatal phthalate exposure and pregnancy outcomes through eicosanoids.…”
mentioning
confidence: 62%
“…We propose an analytical framework (Fig. 1 ) that integrates our previous methodological contributions in environmental risk score construction 16 , 23 , 24 with the aforementioned multivariate mediation analysis methods 19 , 21 . In this framework, we provide a guided discussion on approaches that include one-at-a-time pairwise mediation, exposure dimension reduction, and mediator shrinkage, dimension reduction, and penalization.…”
Section: Introductionmentioning
confidence: 99%
“…This association was more pronounced among male infants than female infants. [51][52][53][54] while others found inconsistent 55,56 or contrasting 49,57 results.…”
Section: Discussionmentioning
confidence: 96%
“…Somewhat surprisingly, we found that phthalate polymers from drugs appear to have similar effects. Some studies have addressed the potential association between environmental phthalate exposure (assessed by biomarkers) and PTB or differences in gestational age 3,[25][26][27][28][29][30][31][32] . Studies that focus on gestational age are less conclusive, whereas studies that address the risk of PTB, support an association.…”
Section: Commentmentioning
confidence: 99%